Lancet Commission on Hypertension group position statement on the global improvement of accuracy standards for devices that measure blood pressure - Sharman, James E; O'Brien, Eoin; Alpert, Bruce; Schutte, Aletta E; Delles, Christian; Hecht Olsen, Michael; Asmar, Roland; Atkins, Neil; Barbosa, Eduardo; Calhoun, David; Campbell, Norm R C; Chalmers, John; et al. (Journal of hypertension, 2020)
: The Lancet Commission on Hypertension identified that a key action to address the worldwide burden of high blood pressure (BP) was to improve the quality of BP measurements by using BP devices that have been validated for accuracy. Currently, there are over 3000 commercially available BP devices, but many do not have published data on accuracy testing according to established scientific standards. This problem is enabled through weak or absent regulations that allow clearance of devices for commercial use without formal validation. In addition, new BP technologies have emerged (e.g. cuffless sensors) for which there is no scientific consensus regarding BP measurement accuracy standards. Altogether, these issues contribute to the widespread availability of clinic and home BP devices with limited or uncertain accuracy, leading to inappropriate hypertension diagnosis, management and drug treatment on a global scale. The most significant problems relating to the accuracy of BP devices can be resolved by the regulatory requirement for mandatory independent validation of BP devices according to the universally-accepted International Organisation for Standardization Standard. This is a primary recommendation for which there is an urgent international need. Other key recommendations are development of validation standards specifically for new BP technologies and online lists of accurate devices that are accessible to consumers and health professionals. Recommendations are aligned with WHO policies on medical devices and universal healthcare. Adherence to recommendations would increase the global availability of accurate BP devices and result in better diagnosis and treatment of hypertension, thus decreasing the worldwide burden from high BP.